Rapid synthesis of oligodeoxyribonucleotides. III. Effect of added carboxylate ion on the efficiency of internucleotide bond formation. Solid-phase synthesis of the dodecanucleotide, d(pT-A-A-C-T-G-C-T-C-A-C-T). - Gait, M J (Nucleic Acids Res, 1979)
In solid-phase oligodeoxyribonucleotide synthesis the addition of benzoic acid to internucleotide phosphodiester bond-forming reactions lowers coupling yields by far greater amount than anticipated on a simple nucleotide-carboxylate molar ratio. High coupling yields were consistently obtained in synthesis of the dodecanucleotide, d(pT-A-A-C-T-G-C-T-C-A-C-T), using rigorously purified nucleotide starting materials. IMAGES: